Critical care nurses' perceptions toward withdrawal of life-sustaining treatments: a phenomenology study - Ibrahim Ahmd Alabd; Sahar Yassien Mohammad; Dalia Ali Ameen (Jurnal Ners)
Introduction: Withdrawing life-sustaining measures involves complex legal and ethical considerations, and few healthcare providers have received specialized training in this area. This study explored critical care nurses' perceptions of withdrawing life-sustaining treatment.